Common electronic origin of superconductivity in (Li,Fe)OHFeSe bulk superconductor and single-layer FeSe/SrTiO3 films - Lin Zhao (Nature Portfolio, 2016)
The mechanism of high-temperature superconductivity in the iron-based materials remains not fully understood. Here, the authors report on ARPES measurements on an FeSe-based bulk superconductor, whose electronic properties are found to be similar to those of single-layer FeSe/STO films.